Identification of Composite Insulator Criticality based on a new Leakage Current Diagnostic Index - Palangar, M.F.; Amin, U.; Bakhshayesh, H.; Ahmad, G.; Abu-Siada, Ahmed; Mirzaie, M. (IEEE, 2021)
In this article, a new method is proposed to identify the health condition of composite insulators through investigating the leakage current (LC) along with the electric potential (EP) and electric field stress (EFS) profiles. In this regard, variations of the LC harmonics and the distribution profiles of the EP and EFS are investigated through a series of experimental and simulation analyses conducted on composite insulators under various environmental and pollution conditions. Fast Fourier transform (FFT) and a COMSOL-multiphysics environment are utilized to analyze this variation. The results reveal a strong correlation between the LC harmonics and the insulator health condition. A new diagnostic criticality index based on the third to the fifth harmonic ratios of the insulator LC is proposed to quantify the composite insulator criticality and predict the likelihood of flashover occurrence. The EP and EFS analyses can be used to provide a complementary diagnosis of the insulator’s health state under severe pollution and humidity conditions. The proposed analysis enables the transmission line network operator to get an insight into the insulators’ functional status, thus improving the network reliability through avoiding insulator failure and adopting a proper condition-based maintenance scheme.